“Gender-Based Water Violence”: Cross-Cultural Evidence for Severe Harm Associated With Water Insecurity for Women and Girls - (:unkn) unknown (SAGE Publications, 2024)
We examined how study participants in Indonesia and Peru viewed the relationship between water insecurity and women's health via thematic analysis of interviews and focus groups. Participants reported that water insecurity led to vaginal infections, misc...
Keywords: Violencia hídrica; Mujeres